Diálogos entre acessibilidade e design universal - Bandeira, Ana Paula Neres de Santana (2016)
Despite the exponencial advances in information and communication technologies, there are still some obstacles when the aim are those users with some kind of disabillity, whether physical, intelectual, visual or hearing. Starting with an analysis of sites – a government one and another oriented to the public with visual impairment – taken as parameters studies of Brazilian legislation on web accessibility and the Principles of Universal Design, it appears that existing solutions, when assimilated in the projects, still incur in discriminatory and inefficient solutions. Starting with the proposal that the very technological advances and the formation of a cyberculture based on post-massive media follows personalizable and customizable solutions, it is proposed a customizable system design for educational e-books user oriented on Universal Design perspectives that are characterized as a totally inclusive design.